Immunization with recombinant GntR plasmid confers protection against Brucella challenge in BALB/c mice. (October 2017) - Li, Zhiqiang; Wang, Shuli; Zhang, Hui; Xi, Li; Zhang, Jinliang; Zhang, Xiaogen; Han, Jincheng; Zhang, Junbo
Abstract: It is essential to improve animal vaccine for brucellosis since conventional vaccines are residual virulent and poor protective effect, limit their applications. To solve these problems, the recombinant DNA vaccines were appeared, which could improve protective immunity and were attenuated to animals. In current research, the recombinant DNA vaccine (pVGntR) based on transcriptional regulator GntR of Brucella abortus ( B. abortus ) was constructed. The results show that pVGntR is significantly more protective than the conventional RB51 vaccine. Immunization with pVGntR increases the production of immunoglobulin G (IgG) and elicits elevated numbers of gamma interferon (IFN-γ) and interleukin-4 (IL-4). These results suggest that pVGntR is a highly efficacious vaccine candidate that confers protection against wild-type B. abortus challenge. Highlights: The pVGntR DNA vaccine can elicit IgG response. The pVGntR DNA vaccine induces cellular responses. The pVGntR DNA vaccine induces protection against B. abortus challenge.